2022
DOI: 10.1038/s41597-022-01739-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of FAIR principles in the IPCC: the WGI AR6 Atlas repository

Abstract: The Sixth Assessment Report (AR6) of the Intergovernmental Panel on Climate Change (IPCC) has adopted the FAIR Guiding Principles. We present the Atlas chapter of Working Group I (WGI) as a test case. We describe the application of the FAIR principles in the Atlas, the challenges faced during its implementation, and those that remain for the future. We introduce the open source repository resulting from this process, including coding (e.g., annotated Jupyter notebooks), data provenance, and some aggregated dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Persistence of this sink in a mesic savanna of Australia is uncertain as it may eventually saturate given nutrient limitations, but thickening is likely to persist for several decades (Scheiter et al, 2015). Regional‐scale model outputs from CMIP6 of the IPCC’s AR6 suggest a small increase in precipitation (Iturbide et al, 2020) as is currently being observed across north‐west Australia. This is in contrast with the savanna and dry forest regions of southern and central America and southern Africa.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Persistence of this sink in a mesic savanna of Australia is uncertain as it may eventually saturate given nutrient limitations, but thickening is likely to persist for several decades (Scheiter et al, 2015). Regional‐scale model outputs from CMIP6 of the IPCC’s AR6 suggest a small increase in precipitation (Iturbide et al, 2020) as is currently being observed across north‐west Australia. This is in contrast with the savanna and dry forest regions of southern and central America and southern Africa.…”
Section: Discussionmentioning
confidence: 98%
“…This is in contrast with the savanna and dry forest regions of southern and central America and southern Africa. Using a standardized precipitation index (SPII‐6), median precipitation is predicted to decrease by 20%–50% for southern Africa and between 30 and 70% for south and central America over the next two decades assuming an SSP5 8.5 scenario (Iturbide et al, 2020). While CO 2 fertilization may offset impacts of declining precipitation, changes to extremes of temperature, evaporative demand and fire climatology may have significant effects on sequestration rate and stability of carbon pools in these extensive tropical ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Main criteria are the existence and shape of glaciers and the existence of glacier lakes. Climate projections for the end of this century are derived from the IPCC WG I Interactive Atlas (Iturbide et al, 2021).…”
Section: Climate Change Impactsmentioning
confidence: 99%
“…Therefore, we combined here different rules to derive the potential role of climate change in these cases and to assess their future occurrence. These rules are specific to the triggers and initial processes affected by climate change and thus consider the permafrost zonation index (PZI), occurrence of glaciers along the process trajectories, observed changes in precipitation (Sun et al, 2021) and projected changes by the end of this century (Iturbide et al, 2021). For the latter, we analyzed changes of annual precipitation sums (PSUM), changes in the highest 1-day (Rx1d) and 5-day (RX5d) precipitation totals for the Representative Concentration Pathway (RCP) 8.5.…”
Section: Potential Climate Change Impactmentioning
confidence: 99%
“…Figure 1. Projected annual mean temperature changes in the MED region relative to the historical period of 1986-2005 under the Shared Socioeconomic Pathways (SSP)-5 scenario with anticipated global warming levels by (a) 1.5 °C, (b) 2 °C and (c) 3 °C within the Coupled Model Intercomparison Project 6 (CMIP6)(Iturbide et al, 2021;Gutiérrez et al, 2021).…”
mentioning
confidence: 99%